2016
DOI: 10.1007/s10658-016-1113-5
|View full text |Cite
|
Sign up to set email alerts
|

DON content in oat grains in Norway related to weather conditions at different growth stages

Abstract: High concentrations of the mycotoxin deoxynivalenol (DON), produced by Fusarium graminearum have occurred frequently in Norwegian oats recently. Early prediction of DON levels is important for farmers, authorities and the Cereal Industry. In this study, the main weather factors influencing mycotoxin accumulation were identified and two models to predict the risk of DON in oat grains in Norway were developed: (1) as a warning system for farmers to decide if and when to treat with fungicide, and (2) for authorit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
51
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 21 publications
(58 citation statements)
references
References 60 publications
5
51
2
Order By: Relevance
“…Nine percent of the samples contained HT2 + T2 levels above the indicative limit set for unprocessed oats (1000 μg kg −1 ), and 25% of the samples contained HT2 + T2 values higher than our more rigorous level of 500 μg kg −1 used in this study. The same samples were also tested for DON contamination (Hjelkrem et al 2017) and no significant (p < 0.05) relationship was observed between the concentrations of the two mycotoxins (μg kg −1 oat grain) in an ordinal regression analysis (using the natural logarithm). A total of 148 weather variables, based on air temperature, rainfall and relative humidity were summarised within each of the ten estimated phenology windows for all 188 oat fields included in this study.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Nine percent of the samples contained HT2 + T2 levels above the indicative limit set for unprocessed oats (1000 μg kg −1 ), and 25% of the samples contained HT2 + T2 values higher than our more rigorous level of 500 μg kg −1 used in this study. The same samples were also tested for DON contamination (Hjelkrem et al 2017) and no significant (p < 0.05) relationship was observed between the concentrations of the two mycotoxins (μg kg −1 oat grain) in an ordinal regression analysis (using the natural logarithm). A total of 148 weather variables, based on air temperature, rainfall and relative humidity were summarised within each of the ten estimated phenology windows for all 188 oat fields included in this study.…”
Section: Resultsmentioning
confidence: 99%
“…Our approach is based on the window-pane methodology (Coakley et al 1982;Kriss et al 2010) that is used to quantify the importance of environmental variables within temporal windows. A similar mathematical model, designed to predict growth stages of oats based on sowing time and weather conditions, was recently developed to quantify the relationship between weather conditions and DON accumulation in Norwegian oats (Hjelkrem et al 2017). In the present study, we identified possible associations between the occurrence of HT2 + T2 toxins in harvested oat grains and weather conditions between sowing and harvest.…”
Section: Discussionmentioning
confidence: 95%
See 3 more Smart Citations